将来の気候変動下におけるティッピングエレメントのティッピングポイントの超過可能性 - 木口雅司; Masashi Kiguchi; 井芹慶彦; Yoshihiko Iseri; 鼎信次郎; Shinjiro Kanae; 沖大幹; Taikan Oki (公益社団法人 土木学会, 2017)
本研究では、地球温暖化に伴う気候変動が進行して、ある臨界点（ティッピングポイント）を過ぎた時点で不連続のような急激な変化が生じて、大きなインパクトをもたらすような気候変動の要素（ティッピングエレメント）の発現可能性について解析した。先行研究で述べられたティッピングポイントを用いて、4つの排出シナリオや緩和目標としての戦略シナリオと、ティッピングエレメントのうち北極海の夏の海氷の喪失とグリーンランド氷床の融解について関連性を導いた。その結果、ティッピングポイントの不確実性があるものの、各排出シナリオでのティッピングエレメントの発現可能性が示された。一方戦略シナリオでは、複数気候シナリオを用いて検討した結果、気候シナリオとティッピングエレメントの両方の不確実性を組み合わせて議論する可能性が示された。 In this study, we analyzed occurrence possibility of tipping elements, what cause a big impact to society, by abrupt transition with passing a tipping point under future climate change. According to tipping point in previous studies, we derived relationship between tipping elemnts (Arctic summer sea-ice loss and melt of Greenland ice sheet), and RCP (Representative Concentration Pathways) using multi-GCMs and Strategic scenarios as mitigation target. As a result, occurrence possibility of tipping elements in each RCP were indicated even though there are uncertainty of tipping point. In case of analysis using strategic scenario, we showed that it is possible to discuss including of uncertainties of climate scenario and tipping element itself.